OPTIMALISASI OKSIGENASI PADA BAYI PREMATUR DENGAN RESPIRATORY DISTRESS SYNDROME MELALUI QUARTER PRONE POSITION: STUDI KASUS - Kunta Taqiyya Ramadhanti Rahayu; Ai Mardhiyah; Windy Rakhmawati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Premature infants are at high risk of Respiratory Distress Syndrome (RDS) due to pulmonary immaturity and surfactant deficiency, leading to impaired oxygenation. The quarter prone position is a non-pharmacological intervention that may enhance respiratory function. This case study aimed to analyze the effect of the quarter prone position on oxygenation status in premature neonates with Respiratory Distress Syndrome. Method: A descriptive case study design using a nursing process approach was applied to one premature neonate diagnosed with Respiratory Distress Syndrome who received respiratory support using Continuous Positive Airway Pressure (CPAP) in a perinatology unit. The quarter prone position intervention was implemented in a structured manner over several days, with continuous monitoring of oxygen saturation and respiratory rate. The findings demonstrated an improvement in oxygenation status, characterized by increased oxygen saturation and stabilization of respiratory rate following the intervention. These results indicate that the quarter prone position contributes to enhanced ventilation effectiveness and reduced respiratory effort in premature neonates with respiratory distress. In conclusion, the quarter prone position is an effective non-pharmacological nursing intervention and may be considered an integral part of neonatal nursing care to optimize oxygenation in premature infants with Respiratory Distress Syndrome.